Pengaruh Lingkungan Kerja, Stres Kerja, dan Beban Kerja Terhadap Kinerja PT. Sakti Mobile Jakarta - Eric Hernawan (Jurnal Kajian Ilmiah, 2022)
In accordance with the vision of "growing and developing into one of the best and committed companies in the telecommunications industry", and the mission of "becoming a partner for all stakeholders and providing the best solutions in the development of telecommunications in Indonesia.". No wonder this company developed rapidly at the beginning of its establishment, but in recent years has experienced a significant decline in performance. It is suspected that this temporary decrease in performance is caused by work stress and workload and a work environment that does not meet the proper requirements. These three independent variables will determine their influence on the performance of PT. Sakti Mobile Jakarta employees either partially or simultaneously using simple regression and multiple regression. Before the regression equation was determined, the validity, reliability, normality, multicollinearity and heteroscedasticity tests were carried out. The magnitude of the effect is done by distributing questionnaires to 85 respondents who are employees of PT. Sakti Mobile Jakarta. The results obtained by the independent variables have a significant effect. either partially or simultaneously. The effect in percent (%) for work environment, work stress and workload (separately is 37.8%., 41.2%. and 20.1%). While the influence in % together is 44.8%.